2012
DOI: 10.1134/s107036321203019x
|View full text |Cite
|
Sign up to set email alerts
|

Electronic and steric effects of substituents on the coordinating properties of porphyrins

Abstract: Kinetics of the formation of zinc complexes of porphyrin with various substituents was studied in acetic acid and pyridine. The introduction of strong electron-withdrawing substituents (nitro groups) to the meso-positions of the porphyrin macrocycle was shown to change the reaction rate by an order of magnitude or less compared to the phenyl-substituted analogs. However, the introduction of a large number of bulky substituents leads to the deformation of the porphyrin ligand and thus affects much stronger the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…Acetic acid has been chosen for the titration procedure since it forms relatively labile solvated complexes of transition metals, which can be easily broken in the presence of the porphyrin macrocycles to form metallocomplexes: thus, for example, 2,3,7,8,12,13,17,18octamethylporphyrin complexation rate constant with Cu 2+ was found to be about 10 5 times higher compared to that measured in pyridine. 32,33 The obtained data on kinetic parameters of Cu-porphyrins formation indicate that electronic effects play the important role in the complexation. Replace of the electron donating substituents in porphyrin 1 for the electron withdrawing ones in the porphyrin 2 leads to almost 100-fold increase in the efficient rate constant k eff of the complexation.…”
Section: Resultsmentioning
confidence: 91%
“…Acetic acid has been chosen for the titration procedure since it forms relatively labile solvated complexes of transition metals, which can be easily broken in the presence of the porphyrin macrocycles to form metallocomplexes: thus, for example, 2,3,7,8,12,13,17,18octamethylporphyrin complexation rate constant with Cu 2+ was found to be about 10 5 times higher compared to that measured in pyridine. 32,33 The obtained data on kinetic parameters of Cu-porphyrins formation indicate that electronic effects play the important role in the complexation. Replace of the electron donating substituents in porphyrin 1 for the electron withdrawing ones in the porphyrin 2 leads to almost 100-fold increase in the efficient rate constant k eff of the complexation.…”
Section: Resultsmentioning
confidence: 91%
“…On the other hand an introduction into a macrocycle of a great number of band meso-substituents which possess a definite volume forces a porphyrine molecule to take nonplanar conformation as it was shown in references [6,[23][24][25]30]. A nonplanar distortion of a porphyrins macrocycle structure results in decrese of molecule aromaticity and in some separation of pyrrole and pyrrolenin fragments.…”
Section: Resultsmentioning
confidence: 98%
“…To date, some attempts have been made in this direction. In our previous works it was shown that nonplanar porphyrin macrocyclic distortions have a great influence on the acid-base properties of porphyrinligand and depend on a solvent nature increase or reduce reaction rate of formation of metalloporphyrins within several orders of magnitude [6,8,[22][23][24][25].…”
Section: Introductionmentioning
confidence: 99%